Hubungan Efikasi Diri Dengan Kemandirian Ditinjau Dari Jenis Kelamin Pada Mahasiswa Fakultas Ilmu Tarbiyah Dan Keguruan - Khairina Siregar (Departement of Mathematics Education, 2023)
independence at the faculty of tarbiyah and teacher training (FITK) in terms of gender, and to determine differences in male and female student learning independence. This study used a quantitative method, with data collection methods through a questionnaire in the form of a Likert scale. Questionnaire is a method of inquiry using a list of statements that must be answered by the subject. Then the measuring instrument scale used in this study is the self-efficacy and independence scale. While gender only uses code 1 for male students and 2 for female students. The results of the study concluded that (1) there is a relationship between self-efficacy and independence in terms of the gender of students of the Faculty of Tarbiyah and Teacher Training. This is obtained from R Squared = .203 with a significance of p = 0.000 (p <0.05); and (2) There are differences in the independence of male and female students in the Tarbiyah and Teacher Training Faculty of UIN SU Medan. This is obtained from the value of F = 32.809 with a significance of p = 0.000 (p <0.05), meaning that there is a significant difference in independence between male and female students in the Faculty of Tarbiyah and Teacher Training.